Address Terms and Addresser-Addressee Relations in Javanese Morning Greetings - Pawiro, Muhammad Ali; Risnawaty, Risnawaty; Hasibuan, Annim; Suhery, Dedy; Raza, Mohd Hamid (JOLLT Journal of Languages and Language Teaching, 2025)
Greetings are always discussed in terms of sociolinguistics, semantics, pragmatics, and communication separately; however, this paper attempts to examine holistic perspectives. The research is especially aimed at discussing Javanese morning greetings which remain important and crucial in the modern era and technology that any Javanese speakers do not switch to using Indonesian or other international languages in communication. This research is qualitative in which data were retrieved from four online websites and four contributors. The population was 130 written utterances, and of that amount, 39 ones were taken as samples using purposive sampling. Data collection was carried out from November 2 to 10, 2022 involving online observation and data were analyzed descriptively. The research shows that, referring to social interactions, morning greetings keep Javanese away from individualism or individualist characteristics and the addressers assume the addressees understand Javanese. Morning greetings have high speech level or high Javanese (kromo inggil) and are not influenced by weather and routine. Only harmony and respect play a role since greetings are written in high speech level. All addressers also assume they feel “at homes” by the use of native language. Kinship titles and names are unavailable or Ф and do not relate to region difference, and sex and race variation. About mode of communication, all greetings use visual channel and involve anonymous addressers and addressees. The addressees’ reception cannot be measured and the greetings fall under linguistic, but not interactional, routines and consist of ‘recounting of one’s mission’ (without apology, gratitude, and thanksgiving as well as non-verbal behavior). It is concluded morning greetings symbolize the honor and do not always specify words concerning the attributes of participants, except the occupation and socioeconomic status, and are not preceded by God’s blessing or shouts.